Prevalence of Mental Health Problems among Diabetic Patients: A Comparison among Gender with Different Types of Diabetes - Muhammad Sajjad; Dr. Aqeel Ahmad Khan (Review Journal of Social Psychology & Social Works, 2025)
Diabetes is considered as a chronic illness and its victims experience many mental health problems. This is an acknowledged fact that when a patient receives an unexpected diabetic diagnosis, they experience stress, anxiety, depression and many other psychological issues. This study was carried out to address the prevalence of mental health issues among diabetic patients and to compare these mental health issues among gender with different types of diabetes. For this purpose a sample of (N=198) diagnosed diabetic patients were included by using purposive sampling method. The level of mental health problems was measured by using three valid and reliable scales. The results from the collected data revealed overall prevalence of mental health issues among diabetic patients but the difference among various types was not significant. However, level of stress was higher among the patients with type-1 diabetes. On the other hand, gender differences showed a higher level of overall mental health issues among female diabetic patients. Hence, the study concluded that the stress is the core psychological cause among the diabetic patients and this should be addressed at initial level to uplift the mental well-being of diabetic patients.